On the issue of translation of Arabic newspaper discourse - Seitmetova, Zh R; Zhiekbayeva А B (Journal of Oriental Studies, 2016)
The paper deals with an analysis of the basic problems that arise during the translation of newspaper from Arab into Russian. Such problems arise as a consistency of differences in lexical, grammatical and stylistic structure of both languages. In this analysis the author tries to estimate not only the translation process and the translation process methodology but also the Arab language particularities that can comprise some difficulties during translation.